Answer :

(cos α + cos β)2 + (sin α + sin β)2


= (cos2 α + 2cos α cos β + cos2 β) + (sin2 α + 2sin α sin β + sin2 β)


Rearranging the terms,


= (cos2 α + sin2 α) + (cos2 β + sin2 β) + 2(cos α cos β + sin α sin β)


= 1 + 1 + 2cos (α – β)


= 2{1 + cos (α – β)}


=


= 4cos2


Comparing with question, λ = 4 (Ans)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics